Potensi Hasil Galur Harapan Kacang Bambara (Vigna subterranea L. Verdcourt) Kondisi Tanam Musim Kemarau - Nurholis, Nurholis; Fatimah, Siti (Rekayasa, 2023)
Legumes play an important role in the food diversification programs in Indonesia. The Bambara bean has a high enough nutritionalvalue and is thus a promising food source for increased production. Bambara beans also have the advantage of being able to grow well on dry land. The activity of assembling superior varieties of Bambara peanut has been carried out since 2012, namely through the selection of local cultivars from various Bambara peanut planting centers, including from Madura. The yield test is the final stage in the assembly of varieties and lines that pass all stages of the test, which will later be submitted for release as new superior varieties. This study aims to test the yield potential of selected lines of Bambara peanut planted during the dry season in Bangkalan, Madura.  This study used a randomgroup design (RAK) with 12 genotypes of Bambara beans and repeated 3 times. The results showed that G12 (CKB-1 UP) is a genome that bears the highest production production among 11 other genotypes with a productivity of 2.28 tons/ha of pods and 109 days after planting (DAT). The number of pods has a high heritability value, so that it can be used as a reference in making a selection. The results of the correlation test showed that the vegetative character had an effect on the yield character.